Resignation of President Andrews (Quarterly Journal of Economics, 1897)
Resignation of President Andrews Get access The Quarterly Journal of Economics, Volume 12, Issue 1, October 1897, Pages 91–94, https://doi.org/10.1093/qje/12.1.91 Published: 01 October 1897